Artificial Insemination: A Reexamination - James, David N. (Philosophy & theology, 1988)
This paper is a comprehensive examination of the ethical issues surrounding artificial insemination. The interests of parents, AI children and society are identified and compared, and a variety of arguments for and against AIH and AID are examined. Although various criticisms of the natural law position are offered, this paper comes to the similar conclusion that donor artiricial insemination is not morally justified.